“LOVING OR LOATHING LYNDA” A PILOT STUDY INVESTIGATION INTO THE INTEGRATION OF VIDEO E-LEARNING RESOURCES WITHIN AN UNDERGRADUATE LEISURE MANAGEMENT DEGREE UNIT - Melhuish, Lynsey (PEOPLE: International Journal of Social Sciences, 2016)
Universities are under increased pressure to respond to the continued development of technology and in incorporating e-learning throughout the Higher Education (HE) environment and infrastructure. This research carried out a pilot case study at Southampton Solent University, focusing on one aspect of e-learning (video tutorials from Lynda.com a global learning resource). Management and leadership video tutorials were selected and integrated into a Level five undergraduate leisure management unit (70 students) delivered over one academic year (14.15) to evaluate the effectiveness of the software as a learning tool for HE. A mixed method triangulation approach was utilized combining analysis of secondary data produced from the Lynda.com monitoring software, alongside a questionnaire (replicated from similar research) through survey monkey and SPSS, in addition to a focus group and collation of open comments from the questionnaire (using content analysis) to explore more qualitative data to enrich the statistical outcomes. The research reinforced previous literature regarding the complex nature of monitoring and evaluating e-learning in HIM. This recognized the need for a systematic approach to the integration of e-learning within an HE curriculum and that clear objectives were needed including whether it is part of formative/ summative assessment or purely optional such as blended learning to enhance the student experience. Results indicated that whilst e-learning may not improve assessment performance it has the power and potential to significantly influence student satisfaction. In an increasingly competitive environment with high student expectations and demands, universities must be seen to be responding to the students ‘digital desires’ [1] of the modern age. Recommendations focused on, access, training and support, quality and relevance of e-learning, establishing incentives, maximizing engagement (the student experience), the need for effective performance monitoring and evaluation and a ‘holistic’ and strategic university wide approach in responding to e-learning in HE.